Themes and Theories Revisited: Perspectives on Processes in Family-Peer Relationships - Gary W. Ladd; Ross D. Parke (MDPI AG, 2021)
Nearly thirty years ago, we invited a consortium of esteemed researchers to contribute to a volume entitled Family-Peer Relations: Modes of Linkage that provided a state-of-the-science appraisal of theory and research within the newly emerging discipline of family-peer relations. The volume's first chapter was titled, "Themes and Theories: Perspectives on Processes in Family-Peer Relationships", and its primary aims were to identify the processes in the family system that were posited to have a bearing on children's development in the peer system (and vice versa), characterize potential mechanisms of linkage, describe extant lines of investigation, appraise empirical accomplishments, and identify issues in need of further investigation. Here, nearly thirty years hence, we are pleased to have the opportunity to reappraise the theory and research on family-peer relations. In this article, we revisit the primary objectives that were addressed in our previously published "Themes and Theories" chapter but do so with the express purpose of evaluating the discipline's progress. Likewise, we also revisit our prior roadmap and associated calls-to-action to update these entities in light of past accomplishments, current limitations, and pressing sociocultural issues and concerns.